Imaging single Rydberg electrons in a Bose–Einstein condensate. (May 2015) - Karpiuk, Tomasz; Brewczyk, Mirosław; Rzążewski, Kazimierz; Gaj, Anita; Balewski, Jonathan B; Krupp, Alexander T; Schlagmüller, Michael; Löw, Robert; Hofferberth, Sebastian; Pfau, Tilman
Abstract The quantum mechanical states of electrons in atoms and molecules are distinct orbitals, which are fundamental for our understanding of atoms, molecules and solids. Electronic orbitals determine a wide range of basic atomic properties, allowing also for the explanation of many chemical processes. Here, we propose a novel technique to optically image the shape of electron orbitals of neutral atoms using electron–phonon coupling in a Bose–Einstein condensate. To validate our model we carefully analyze the impact of a single Rydberg electron onto a condensate and compare the results to experimental data. Our scheme requires only well-established experimental techniques that are readily available and allows for the direct capture of textbook-like spatial images of single electronic orbitals in a single shot experiment.